Breaking of seed dormancy, plantlet regeneration and antioxidant activities of Bunium persicum - Emamipoor, Yousef (2012)
Bunium persicum (Boiss) Fedtsch is a valuable medicinal plant that is facing extinction. A study was conducted to adopt various strategies and techniques to conserve and protect the biodiversity of B. persicum. Germination of dormant seeds and also maturation of seedlings under in vitro condition to overcome seed dormancy and reduce the juvenile period were studied. Then, the efficiency of direct and indirect shoot regeneration, the capacity of somatic embryogenesis and development of micropropagation methods were investigated. In addition, the antioxidant potential, total phenolic compounds and flavonoid contents of seeds were compared with explants and their related calli. The seeds were treated at room (25 °C) and chilling (2-5 °C) temperatures with or without plant growth regulators (PGRs). The germination rate of dormant seed was 54.7, 46.7 and 53.3% under moist-chilling, moist-room with 35.2 mg/L gibberellic acid (GA3) and moist-chilling with 1.4 mg/L thidiazuron (TDZ) conditions respectively. In addition, results showed that treatment of seeds with a combination of 1.4 mg/L TDZ with 35.2 mg/L GA3 under moist-chilling conditions caused maximum seed germination, which was 93.7%. Furthermore, transferring of germinated seeds to Murashige and Skoog (MS), Gamborg (B5), Driver and Kuniyuki (DKW) and MSB (MS minerals with B5 vitamins) for maturation demonstrated that ½ MSB media was the most suitable medium for seedling development. Successful direct regeneration of B. persicum obtained 14.5 ± 1.5 shoots per root explant on MSB medium supplemented with 0.02 mg/L methyl jasmonate (MJ). Application of root, corm and leaf explants from six-month-old seedlings on MSB medium supplemented with various auxins showed that root-derived and corm-derived calli on MSB medium supplemented with 1.0 mg/L 2,4-dichlorophenoxyacetic acid (2, 4-D) by 77.1% and 74.9% respectively induced somatic embryogenesis calli. The somatic embryos transferred to medium supplemented with different concentrations of benzylaminopurine (BAP), kinetin, spermidine, forchlorfenuron (CPPU), chlormequat chloride (CCC), paclobutrazol (PBZ), casein hydrolysate (CH), poly ethylene glycol (PEG) and banana powder, led to maximum plantlet regeneration, which was 65.8 ± 2.6 obtained in ½ MSB medium supplemented with 20 g/L banana powder. Consequently, induction of somatic embryogenesis under 1.0 mg/L 2,4-D was found to be more suitable than other auxins and capacity of banana powder for plantlet development by having indol acetic acid (IAA), cytokinins and gibberellins (GAs) was more than other additives and PGRs. Successful indirect shoot regeneration of B. persicum was obtained from culture of leafderived callus on MSB medium supplemented with 0.4 mg/L 2,4-D. The callus was implanted on ½ MSB medium supplemented with 0.2, 0.4, 0.6, 0.8, and 1.0 mg/L various cytokinins including BAP, kinetin, isopentyl aminopurine (2iP) and zeatin. Results indicated that the most suitable cytokinins for shoot regeneration were 0.6 mg/L kinetin with 34.2 ± 0.6 plantlets per culture. In addition, CPPU, TDZ, spermidine and additives including banana powder, yeast extract and casein hydrolysate influenced callus proliferation more than regeneration. Subsequently, results indicated that efficiency of embryogenesis callus was more than indirect and direct shoot regenerated calli. Also, the effect of different concentrations of sucrose, BAP, PBZ and GA3 on size of B. persicum corms was investigated. Results showed that 90 g/L sucrose with 164.9 ±2.8 g corm fresh weight (FW) was the most suitable sucrose concentration for growth of corm and shoot numbers. The antioxidant activity, total phenolic compounds and flavonoids of seed were compared with root, corm, leaf and their related calli. Results of FRAP assay (based on trolox equivalent) showed that leaf segments of six-month-old B. persicum with 16.14 mg TE/ g DW had maximum antioxidant activity. Also, result of DPPH assay (based on gallic acid equivalent) for derived calli indicated that corm-derived callus on medium supplemented with 1.0 mg/L NAA (CN) with 12.61 mg GE/g DW showed maximum scavenging of free radicals. However, CN with 18.72 mg GE/g DW had maximum phenolic compounds and root-derived callus under 1.0 mg/L picloram (RP) had maximum flavonoid, which was 7.50 mg RE/g DW. The results showed that not only seed but also leaf, corm, root and their related derived callus could be used as natural plant antioxidants. However, B. persicum seeds had higher amounts of naringenin (170.3 μg/ g DW), kaempferol (132.7 μg/ g DW) and quercetin +(120.3 μg/ g DW), but leaves had higher amount of naringin (240.6 μg/ g DW), corms had higher amount of naringinin (146.7 μg/ g DW) while roots had higher amounts of rutin (160.6 μg/ g DW). Results showed that a combination of GA3 (35.2 mg/L) and TDZ (1.4 mg/L) with 93.7% breaking of seed dormancy and subsequent seedling maturation on ½ MSB medium was the suitable method for cultivation via seed. The result also showed that direct regeneration from root explants with 14.5 ± 1.5, indirect shoot regeneration from leafderived callus with 34.2 ± 0.6 and indirect somatic embryodenesis from root-derived callus with 65.8 ± 2.3 plantlets/culture respectively could be reliable methods for B.persicum regeneration. Furthermore, leaf and corm-derived callus with 16.1 mg TE/g DW and 11.2 ± 0.1mg GE/g DW antioxidant activity respectively, were found to be suitable as seed replacement. The presence of various flavonoids in seeds rather than leaf, corm and root could be related to more activity of flavonoid biosynthesis enzymes in seeds.